Intrusion of the Kuroshio Subsurface Water in the southern East China Sea and its variation in 2014 and 2015 traced by dissolved inorganic iodine species. (July 2018) - Zhou, Peng; Song, Xiuxian; Yuan, Yongquan; Wang, Wentao; Chi, Lianbao; Cao, Xihua; Yu, Zhiming
Highlights: Dissolved inorganic iodine in the entire southern East China Sea were determined. Kuroshio Subsurface Water (KSSW) can be well traced by dissolved inorganic iodine. The KSSW intrusion outside the 100-m isobath in the East China Sea was revealed. Interannual variation and ecological effects of the KSSW intrusion were discussed. Abstract: The circulation systems and ecological environment of the East China Sea (ECS) are greatly influenced by the Kuroshio. The nutrient-rich Kuroshio Subsurface Water (KSSW) has been subject to considerable research attention, but the intrusion pathway, extent and variation of the KSSW over the entire southern ECS shelf are still debated. In June 2015, the dissolved inorganic iodine species (DIIS) were determined, and hydrographic data were collected and analyzed in the southern ECS. Analysis of the collected data suggests that the KSSW mainly intrudes onto the ECS shelf from northeast of Taiwan and bifurcates into a nearshore branch and an offshore branch. The nearshore branch ultimately appears in the subsurface layer within the 50-m isobath off the Zhejiang coast, north of 30 °N, and the offshore branch flows along the 100-m isobath and covers the area outside the 80-m isobath. Another KSSW intrusion along the shelf edge is located at ∼28 °N. This additional KSSW intrusion is weaker, and the offshore area in the southern ECS is mainly influenced by the KSSW intrusion northeast of Taiwan. Compared with the KSSW intrusion on the ECS continental shelf (depth < 100 m) in May 2014, the KSSW intrusion northeast of Taiwan in June 2015 was shifted seaward, had a greater geographical reach and intruded farther north off the Zhejiang coast. The KSSW intrusion in the nearshore area off the Zhejiang coast may promote a decrease in dissolved oxygen (DO) in the bottom water as well as the growth of phytoplankton in the upper water. The expansion of the range of the KSSW intrusion northward in 2015 led to the movement of the low-DO, high-chlorophyll area farther north in 2015 relative to its position in 2014 and may have contributed to the variations in hypoxia and algal blooms.